The nutritional profile of high-performance junior soccer players in Western Cape, South Africa - Hoosen, F. (2013)
Very little data exists regarding the nutritional status of adolescent soccer players and there is no national data regarding this population. Aim: The aim of this study was to investigate the dietary intake and anthropometric profile of N=39 male, high-performance, adolescent soccer players who are of mixed race (14 -18 years of age), during the competitive season. Methods: The study design was a descriptive, observational study with an analytical component. A quantified food frequency questionnaire (QFFQ), which has been validated for athletes, was used to characterise their nutritional intake in terms of energy (kCal), macronutrient as well as micronutrient intake. Interpretation of anthropometric data included plotting and interpreting growth indicators such as height-for-age, body mass index (BMI)-for-age, tricep skinfold-for-age, subscapular skinfold-for-age, sum of skinfolds-for-age, arm muscle area (AMA)-for-age, arm muscle circumference (AMC)-for-age, arm fat area (AFA)-for-age and percentage body fat. Results: The anthropometric data showed that most of the players had an adequate height-for-age (100%, N=39) and BMI-for-age (87.2%, N=34). The mean percentage body fat was 10.9±3.5%. The majority of players` skinfold thickness measurements were above the 85th percentile for triceps (56.4%, N=22), subscapular (59.0%, N=23) as well as the sum of two skinfolds (triceps and subscapular), (72.0%, N=28), AMA (82.1%, N=32), AMC (56.4%, N=22) and AFA (56.4%, N=22). Daily minimum and maximum mean energy expenditure was between 3146.9±213.4 and 3686.4±250.0 kcal while daily mean energy intake was 4374.0±1462.4 kcal. Protein (156±53 g/day), carbohydrate (CHO) (557±172 g/day), total fat (149±67.8 g/day) and cholesterol (546±230 mg/day) intake were all above levels recommended for athletes. The mean micronutrient intake met the estimated average requirement (EAR) or adequate intake (AI) for all nutrients. Players who were more physically active displayed more favourable anthropometric indices which included body weight, BMI, body fat indices as well as muscle mass indices, despite having a greater total energy intake (TEI). This difference did however not reach statistical significance. Supper was the most regularly consumed meal (97.4%, N=38). The majority of players (61.5%, N=24) ate breakfast daily with only 5.1% (N=2) who never ate breakfast. However, 20.5% (N=8) of the players only ate breakfast 3 days a week. Conclusion: Although most of the players had a normal body weight and BMI, they were predominantly categorised as above average according to indices of body fat. Body muscle indices was categorised as above average for most players suggesting a beneficial finding in terms of sporting performance. The mean TEI, CHO, protein intake and fat intake were all above the recommended levels for athletes. The mean intake of all vitamins and minerals met the EAR/AI. Players who were more physically active displayed more favourable anthropometric indices, despite having a higher TEI. Although this study population exhibited no evidence of stunting, indicating that the players were well nourished (in terms of sufficient macronutrients and micronutrients), they are at risk of being over-nourished which may negatively impact sporting performance as well as overall health.